The Interconnection of Social Intelligence and the Attitude of People to Dangers - Georgievich, Maralov Vladimir (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The relevance of the problem is caused by the importance of identification of factors that determine the existence of different types of people’s attitudes to dangers, which makes it possible to explain and predict their behavior from the positions of security. It was suggested that social intelligence is one of the most important factors. The goal of the study is the identification of psychological features of the relationship between the social intelligence and people’s attitudes to dangers. Materials and Methods: During the research, we used the theoretical (analysis, specification, and generalization) and empirical methods of data collection. As diagnostic tools, we used special techniques to identify the types of people’s attitudes to dangers and social intelligence. Taking part in the study were 292 participants of different gender, education, and employment aged from 19 to 50 (their average age: 30.3). Results of the Study: It was found that social intelligence is closely related to the type of attitude of people to dangers. To a greater extent, this relationship manifests itself in the choice of adequate or inadequate ways of responding to dangerous situations than in the manifestations of sensitivity to threats. We also discovered some differences in men and women with different levels of social intelligence, which were manifested in the ability to adequately or inadequately respond to dangers. In particular, men with low social intelligence more often ignore dangers while and women tend to exaggerate their significance. Discussion and Conclusions: It is shown that inadequate response manifested in the forms of exaggeration or understatement of the significance of threats in people with a low level of social intelligence performs a protective function acting as a compensation for the inability of an individual to understand situations and to correctly assess them from a security standpoint. The obtained data can be used in psychological counseling of men and women as well as in the work of psychological services in the process of formation of people’s adequate attitudes to dangers.